2015
DOI: 10.1308/rcsann.2015.0017
|View full text |Cite
|
Sign up to set email alerts
|

Parastomal evisceration as an extremely rare complication of a common procedure

Abstract: The creation of an abdominal stoma is a common procedure performed as part of the treatment for many conditions. Common complications include poor stoma siting, high output, skin irritation, ischaemia, retraction, parastomal hernia and prolapse. An extremely rare stoma complication is parastomal evisceration. We present a case of a 48-year-old woman who presented to us with parastomal evisceration as a late complication of a transverse colostomy. It is the second case reported as a complication of this procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…due to COPD) may have also contributed. Lolis et al [7] reported a patient with similar contributory factors in a patient with a parastomal hernia and a chronic colostomy prolapse.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…due to COPD) may have also contributed. Lolis et al [7] reported a patient with similar contributory factors in a patient with a parastomal hernia and a chronic colostomy prolapse.…”
Section: Discussionmentioning
confidence: 92%
“…Parastomal evisceration is a very rare complication of stomas and to date, only ten cases have been reported worldwide. Most of the previously published cases were associated with ileostomies [4][5][6] and four were reported in association with colostomies [7][8][9][10].The majority of the cases were associated with stoma prolapse or parastomal hernia and one within the immediate post-operative period [10].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent indication for colostomy was rectal cancer (1,3,13); the indication for colostomy was extensive hidradenitis suppurativa of the perineum in another case-report (5). Evisceration occured within a time span of 5 (5) to 18 months (13).…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of our study we excluded ileostomy-related parastomal eviscerations and focused on conditions related to colostomy evisceration. We reviewed four articles concerning 4 case reports of late evisceration (1,3,5,13) and three articles on 4 case reports (4,6,7) presenting early postoperative para-stomal evisceration after colostomy (within one month after creation of the colostomy). All case reports were published since 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation